Expression of Normally Repressed Myosin Heavy Chain 7b in the Mammalian Heart Induces Dilated Cardiomyopathy - Angela K. Peter; Alberto C. Rossi; Massimo Buvoli; Christopher D. Ozeroff; Claudia Crocini; Amy R. Perry; Ada E. Buvoli; Lindsey A. Lee; Leslie A. Leinwand (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background In mammals, muscle contraction is controlled by a family of 10 sarcomeric myosin motors. The expression of one of its members, MYH7b, is regulated by alternative splicing, and while the protein is restricted to specialized muscles such as extraocular muscles or muscle spindles, RNA that cannot encode protein is expressed in most skeletal muscles and in the heart. Remarkably, birds and snakes express MYH7b protein in both heart and skeletal muscles. This observation suggests that in the mammalian heart, the motor activity of MYH7b may only be needed during development since its expression is prevented in adult tissue, possibly because it could promote disease by unbalancing myocardial contractility. Methods and Results We have analyzed MYH7b null mice to determine the potential role of MYH7b during cardiac development and also generated transgenic mice with cardiac myocyte expression of MYH7b protein to measure its impact on cardiomyocyte function and contractility. We found that MYH7b null mice are born at expected Mendelian ratios and do not have a baseline cardiac phenotype as adults. In contrast, transgenic cardiac MYH7b protein expression induced early cardiac dilation in males with significantly increased left ventricular mass in both sexes. Cardiac dilation is progressive, leading to early cardiac dysfunction in males, but later dysfunction in females. Conclusions The data presented show that the expression of MYH7b protein in the mammalian heart has been inhibited during the evolution of mammals most likely to prevent the development of a severe cardiomyopathy that is sexually dimorphic.